2020
DOI: 10.14715/cmb/2020.66.4.13
|View full text |Cite
|
Sign up to set email alerts
|

Achillea spp.: A comprehensive review on its ethnobotany, phytochemistry, phytopharmacology and industrial applications

Abstract: The genus Achillea genus houses more than 100 species, a number of them are popularly used in traditional medicine for spasmodic gastrointestinal, gynecological and hepatobiliary disorders, hemorrhages, pneumonia, rheumatic pain, inflammation, wounds healing etc. Members of the genus contain a wide variety of volatile and non-volatile secondary metabolites, including terpenes, polyphenols, flavonoids and others. Multiple studies have assessed the biological effects and other aspects of Achillea spp. In a numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 162 publications
1
15
0
2
Order By: Relevance
“…In studies on the A. arabica plant, it has been reported that the plant contains antioxidant compounds and major essential fatty acids such as p-cymene, piperitone, camphor and 1,8cineole (Mottaghi et al 2016;Kaffash et al 2020). Similarly, in different studies, it has been reported that Achillea species are quite rich in terms of phenolic and sesquiterpene lactone compounds (Salehi et al 2020) such as 𝛼-terpinene (41%), p-cymene (13%) (Dehghan and Elmi 2015), 1,8-cineole (9-37%), camphor (16-30%) (Morteza-Semnani et al 2005), piperitone (35%) and eucalyptol (13%) (Sökmen et al 2004).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In studies on the A. arabica plant, it has been reported that the plant contains antioxidant compounds and major essential fatty acids such as p-cymene, piperitone, camphor and 1,8cineole (Mottaghi et al 2016;Kaffash et al 2020). Similarly, in different studies, it has been reported that Achillea species are quite rich in terms of phenolic and sesquiterpene lactone compounds (Salehi et al 2020) such as 𝛼-terpinene (41%), p-cymene (13%) (Dehghan and Elmi 2015), 1,8-cineole (9-37%), camphor (16-30%) (Morteza-Semnani et al 2005), piperitone (35%) and eucalyptol (13%) (Sökmen et al 2004).…”
Section: Discussionmentioning
confidence: 80%
“…Achillea genus, which belongs to the Asteraceae family, consists of more than 100 species, The Achillea species are used for treatment for many diseases such as gynecological and hepatobiliary disorders, rheumatic pain, spasmodic gastrointestinal, pneumonia, hemorrhages, in ammation and wound healing in folk medicine (Wichtl 2002;Burk et al 2010). Members of this genus contain volatile oil and other secondary metabolites, including terpenes (especially sesquiterpene lactones), avonoids, polyphenols and others (Salehi 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A landmark study by Si et al [11] was meticulously planned, including the structures and biological properties of known phytochemicals from Achillea spp., followed by the comprehensive summary of Saeidnia et al [14] and other numerous reviews on this topic [12,13]. Therefore, ten years after the last overviews by Si et al [11] and Saeidnia et al [14] (2006 and 2011, respectively), the present review aims to provide and summarize the existing knowledge on the genus Achillea, focusing on traditional uses, phytochemistry and pharmacological activities.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, triterpenes, sterols, coumarins and phenolic acids were also reported [11]. Additionally, there are a lot of studies reporting the volatile constituents of the genus, which have been summarized in recent years [12,13]. Essential oils, isolated from Achillea spp., as secondary metabolites involve complex mixtures that also contribute significantly to the observed biological activities against a variety of ailments, and especially intestinal disorders and inflammatory diseases [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation